PENGARUH LOKASI, KELENGKAPAN PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN AYAM GEPREK GOLD CHICK TIBAN - Artono, Tania Gabriella Assajdah Roeky; Silitonga, Frangky; Kartika Cahayani (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2024)
The aim of the research is to determine the influence of location, product availability and service quality on consumer decisions at Ayam Geprek Gold Chick Tiban. The research method used is a quantitative method with data collection techniques carried out using questionnaires, observation, interviews and literature review. The sampling technique uses the Accidental Sampling technique which takes respondents who happen to be on Tuesdays and Saturdays. The results of the analysis show that Location (X1) has an effect on consumer satisfaction of 4,023, Product Completeness (X2) has an effect on consumer satisfaction of 3,319, Service Quality (X3) has an effect on consumer satisfaction of 3,054, and the most significant of the three is 87,864. It is hoped that future researchers will perfect the parts of the variables that have not been studied within the scope of this research